Class attendence system using rapid web application development / Noor Aishah Nabila Muhamad Nizam - Muhamad Nizam, Noor Aishah Nabila (2020)
Tracking students' attendance is an important issue. It is important to monitor students' overall performance in the classroom as well as in their studies. Dealing with students' attendance during classes has to turn out to be a tough challenge. The current practice to record attendance in most universities is through a manual procedure by using a paper-based approach to collect students' attendance. This practice will lead to inefficient handling of documents and difficult to track the students' attendance performance in class. For the stated reason, this project proposed an efficient student attendance system based on rapid web application development. There are three objectives for this research which needed to be achieved, those are to identified the appropriate approach for the current development of students' attendance system, to design the attendance system for students using rapid web application development, to evaluate the effectiveness using technology acceptance model. By using a rapid application development method, it would simplify the application so the rework is greatly reduced and cost overrun is avoided to a large extent. The finding of this project will redound to the benefits of the lecturers in universities, given that this project is designed to overcome the current problem by developing an effective attendance system using rapid web application development that can solve the attendance problem using OpenXava technology. In the future, an improvement can be made such adding a several roles to the system.